Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1159/000176506
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Glycoproteins in the Intestinal Mucosa

Abstract: To determine the effect of diets on the biosynthesis of glycoproteins in the intestinal mucosa, male Sprague-Dawley rats were fed, ad libitum, high-carbohydrate, high-fat and high-protein diets. In in vivo methodology, the animals from each dietary group received an intraperitoneal injection of [14C]-fucose, or [14C]-galactose or [14C]-glucosamine. Incorporated radioactivity was detected in the different subcellular fractions. In in vitro methodology, five glycosyl-transferases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…It is reported that both quantity and quality of dietary components induce modifications in membrane glycosylation in the intestine [5]. Membrane fucosylation and sialylation processes are influenced by variations in the carbohydrate, lipid and protein contents of the diet in weanling [6] and adult animals [7]. Thus, any change in the membrane oligosaccharides in the intestine could influence the functional characteristics of the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that both quantity and quality of dietary components induce modifications in membrane glycosylation in the intestine [5]. Membrane fucosylation and sialylation processes are influenced by variations in the carbohydrate, lipid and protein contents of the diet in weanling [6] and adult animals [7]. Thus, any change in the membrane oligosaccharides in the intestine could influence the functional characteristics of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Biol et al [6] reported enhanced fucosyltransferase activity in rat intestinal mucosa in response to the feeding of a high-protein diet. The reported increase in fucosyltransferase activity in response to HP intake may be due to modification of enzyme biosynthesis [26] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of the dolichol pathway of the glycoprotein mannosylation gave rise to sev eral works dealing with the adaptation of this compound to various diets, either in the liver [18,19], the adipose tissue [13] or the pan creas [3. 4], In a previous paper [5], we described large variations of intestinal glycosyltransferase activities, which do not in volve dolichol intermediates, to nutritional factors: activation of fucosyltransferase ac tivity by a high-protein diet and inhibition by a high-fat diet. In this last case, an additional direct regulatory effect of the free fatty acids provided by the diet was demonstrated [2], In these studies, however, supplemented diets were used so that nutritional interpretation was not obvious in view of the high varia tions in the energy/protein ratios of the diets, inducing very different nutrient intakes.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplements have gained attention in recent years. Soluble dietary oligosaccharides extracted from various sources have been shown to promote the proliferation of specific beneficial bacterial groups and thus are termed prebiotics [18,19,20,21,22,23]. Examples of prebiotics include fructooligosaccharides, galactooligosaccharides, arabinose, galactose, inulin, raffinose, mannose, lactulose, stachyose, mannanoligosaccharides, xylooligosaccharides, palatinose, lactosucrose, glycooligosaccharides, isomaltooligosaccharides, and soybean oligosaccharides [20,24,25,26].…”
Section: Introductionmentioning
confidence: 99%